História, narração e identidade judaica em A Gloriosa Família: o tempo dos Flamengos de Pepetela - Machado, Célia Maria Borges (2019)
The text presented here results from an analysis of the work The Glorious Family (1997) by the Angolan writer Artur Carlos Maurício Pestana dos Santos – Pepetela. The novel is inscribed in what contemporary theorists have called postcolonial writing, and depicts the seven years of Dutch rule in Luanda, from 1641 to 1648, a period of wars and suffering for the locals. In order to refigure this past, the writer uses a contemporary literary technique, the Historiographic Metafiction, through which he was able to construct the discourse of the narrator, a mute and illiterate slave, with humor, irony and a lot of creativity. Our analysis focused on the figure of this narrator, the discursive strategies invested by the author to give shape to the literary text and the figuration of characters, especially Jews present in the work. These aspects proved to be a political practice of Pepetela's Literature, whereby the writer gives prominence to the marginalized subjects, and denounces, therefore, what official History silenced throughout the period of colonization in Africa: the neglect towards those who constituted and built the wealth of their nation. Once the scope of this work was delineated, we focused on the following post-colonial and African studies: Ana Mafalda Leite´s, Benedict Anderson´s, Elena Bruggioni´s, Inocência Mata´s, João Adalberto Campato Jr´s, Linda Hutcheon´s, Thomas Bonnicci´s. Regarding narrator and narrative studies, we focused more directly on Isaías Carvalho´s, Walter Benjamin´s and Silviano Santiago´s. In order to better understand issues related to Judaism, we worked with the following studies: Kênia Pereira´s, Toby Green´s, Moacyr Scliar´s, Anita Novinsky´s, Antonio José Saraiva´s and Élcio Loureiro Cornelsen´s. With the purpose of building a more consistent understanding of myth and religion, we made use of Mircea Eliade´s, Virgílio Coelho´s and Michel de Certeau´s studies, among others.